Diagnosing childhood Tuberculosis in rural clinics in Mpumalanga Province, South Africa - S.C. Vellema (AOSIS, 2008)
Tuberculosis is a major global public health challenge and disease in young children is particularly severe. Diagnosing tuberculosis in children is complex as clinical presentation is often atypical and available diagnostic modalities are imperfect. Diagnosis is particularly challenging in developing countries where resources and access to sophisticated facilities are limited. The South African primary health care system requires frontline nurses to be equipped to suspect, diagnose and treat children with tuberculosis, but their capacity to diagnose childhood tuberculosis is unknown. Relatively low rates of childhood tuberculosis notification suggested that tuberculosis may have been under-diagnosed in Mpumalanga Province.